Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Di Sektor Industri Dasar Dan Kimia Yang Terdaftar Di BEI Periode 2020-2024 - Nurfadjriani Bahar; Hariany Idris; Samirah Dunakhir (UNIVERSITAS DHARMAWANGSA, 2026)
This analyze the Influence of Good Corporate Governance and Corporate Social Responsibility on Company Value in the Basic and Chemical Industry Sector Listed on the Indonesia Stock Exchange for the 2020-2024 Period. The variables of this study are Good Corporate Governance (X1) which is measured using Managerial Ownership, while the Corporate Social Responsibility variable (X2) is measured by the Corporate Responsibility Disclosure Index and the Company Value variable (Y) is measured by Price to Book Value. The population of this study is 85 basic and chemical industry sector companies listed on the IDX in 2020-2024 while the sample is 13 companies taken using a purposive sampling technique. Quantitative data analysis techniques used are descriptive analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that: (1) based on the t-statistical test, the GCG value obtained is t count 5.306 with a significance value of 0.000 <0.05. This shows that managerial ownership has a significant effect on company value so that H1 is accepted, (2) based on the t-statistic test, the corporate social responsibility value obtained is t count 5.377 with a significance value of 0.000 < 0.05.